Evaluation of caregivers’ first time use of a seamless deployment platform - Wagner, Stefan (2016)
The CareStore project is investigating the feasibility of creating an open and flexible infrastructure for facilitating seamless deployment of healthcare devices and applications. Such seamless deployment is relevant in order to optimize work flows and save resources, but must deliver a calm user experience in order to be effective. This paper describes a study with the aim of investigating the user experience of non-technical care staffs' first time use of a technology platform designed for supporting seamless deployment of telemedicine and ambient assisted living equipment in care facilities. We invited eight caregivers working at an assisted living ward of a North German care facility, two nurses and six otherwise trained caregivers, to go through a realistic deployment and usage scenario. The specific objectives were to: i) evaluate the feasibility of the system during first time use, and ii) gain insights into the caregivers understanding and user experience of the technology. Results indicate that the caregivers could effectively use the touch-to-install deployment system to deploy a new healthcare device and carry through measurements with the device. Also, the nurses found the system effective and easy to use in a first time context, and were optimistic about future possibilities with the system. However, more work is needed to assess the longitudinal effects of this type of seamless deployment technology, including field studies of actual daily usage.